Pengaruh penggunaan media interaktif benime dalam pembelajaran matematika terhadap minat belajar dan hasil belajar siswa - Uyun, kurrotul; Liesdiani, Mety (Papanda Publisher, 2025)
This study aims to examine the impact of using Benime interactive media on students' interest and learning outcomes in mathematics. A quantitative method was employed using a pre-experimental One-Group Pretest-Posttest design. The participants were students of class IX-A at SMP Sabilush Sholihin Socah, selected through random sampling. Instruments used included a questionnaire to assess learning interest and a multiple-choice test to evaluate learning outcomes. The data were analyzed using the Shapiro-Wilk test for normality and Box’s M test for homogeneity. Further analysis involved simple linear regression for learning interest and a paired sample t-test for learning outcomes, using SPSS version 25. The findings revealed that Benime interactive media had a significant positive effect on both students’ interest and outcomes. The regression test showed a significance value of 0.000 (p < 0.005) for interest, and the t-test also indicated a significance value of 0.000 (p < 0.005) for outcomes. Students reported that the animated and visual features of Benime made the material easier to understand and more enjoyable. These results support previous research suggesting that interactive media can enhance student motivation, comprehension, and academic performance. Learning becomes more effective when students are actively engaged through technology. Therefore, Benime can serve as an effective alternative in mathematics education, especially in addressing challenges related to low interest and achievement. This study highlights the importance of incorporating technology-based media to improve the learning experience, particularly in mathematics, which is often considered a difficult subject. Innovative tools like Benime offer new possibilities for making learning more meaningful and student-centered. Keywords: Benime, interactive media, learning interest, learning outcomes